2000
DOI: 10.1084/jem.192.3.381
|View full text |Cite
|
Sign up to set email alerts
|

The Rho Family Guanine Nucleotide Exchange Factor Vav-2 Regulates the Development of Cell-Mediated Cytotoxicity

Abstract: Previous pharmacologic and genetic studies have demonstrated a critical role for the low molecular weight GTP-binding protein RhoA in the regulation of cell-mediated killing by cytotoxic lymphocytes. However, a specific Rho family guanine nucleotide exchange factor (GEF) that activates this critical regulator of cellular cytotoxicity has not been identified. In this study, we provide evidence that the Rho family GEF, Vav-2, is present in cytotoxic lymphocytes, and becomes tyrosine phosphorylated after the cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 46 publications
2
47
0
Order By: Relevance
“…Our results are also consistent with evidence suggesting differential regulation of downstream functions by the hematopoietic-specific Vav1 and widely expressed Vav2 isoforms, which are large multidomain proteins and only 55% homologous (74). In Jurkat T cells, antigeninduced activation of nuclear factor of activated T-cells-or NFB-dependent transcriptional pathways is strongly potentiated by overexpression of Vav1 but not Vav2 (75,76). Furthermore, studies of Vav-deficient mice indicate that Vav1 and Vav2 differentially regulate various lymphocyte functions (74,77,78).…”
Section: Activation Of Endogenous Rac1 By Transgenic Expression Of Rasupporting
confidence: 79%
“…Our results are also consistent with evidence suggesting differential regulation of downstream functions by the hematopoietic-specific Vav1 and widely expressed Vav2 isoforms, which are large multidomain proteins and only 55% homologous (74). In Jurkat T cells, antigeninduced activation of nuclear factor of activated T-cells-or NFB-dependent transcriptional pathways is strongly potentiated by overexpression of Vav1 but not Vav2 (75,76). Furthermore, studies of Vav-deficient mice indicate that Vav1 and Vav2 differentially regulate various lymphocyte functions (74,77,78).…”
Section: Activation Of Endogenous Rac1 By Transgenic Expression Of Rasupporting
confidence: 79%
“…This difference may potentially cause a different binding specificity of the two SH2 domains for phosphotyrosine-containing proteins. We have previously shown that both Vav-1 and Vav-2 overexpression increases cell-mediated cytotoxicity in NK and T lymphocytes (9,24). However, Vav-1, but not Vav-2, selectively controls the NFAT/AP-1-dependent transcription in T cells (24), which indicates that the two isoforms do not have simply a redundant function.…”
Section: Discussionmentioning
confidence: 99%
“…38 Notably, rac1, ERK1/2 effectors, and Ca ϩϩ elevation critically control cytolytic granule polarization and exocytosis. 9,19,[39][40][41][42][43] Our results demonstrate that SHIP-1 could limit activation signals necessary for CD16-dependent cytotoxic function. Overexpression of SHIP-WT reduced CD16-mediated cytotoxicity and the functional catalytic domain of SHIP-1 is required, in that overexpression of the phosphatase inactive mutant did not affect the cytotoxic function.…”
Section: Discussionmentioning
confidence: 99%